2022
DOI: 10.12913/22998624/155188
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the Structural and Physical Properties of the Thermoplastic Starch Film with Kaolinite and Beeswax Addition

Abstract: The aim of the study was to investigate the influence of kaolinite (KA) and beeswax (BW) addition on the structural and physical properties of thermoplastic starch (TPS) films. The casting method was applied and glycerol was used as a plasticizer. Microstructure analyzes were made by a stereoscopic and a scanning electron microscope. Tensile tests were carried out under static load conditions at three different deformation velocities of V = 0.0001, 0.001, and 0.01 m/s. The studies of surfaces characteristic we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 45 publications
0
5
0
Order By: Relevance
“…The casting technique was used to prepare films of hydrolyzed corn starch powder, glycerol, and glacial acetic acid according to the methodology of Beer-Lech et al [31]. First, 20 ± 5 g of hydrolyzed corn starch powder was mixed with 150 ± 5 mL of distilled water at 50 ± 5 • C to prepare the film-forming solution.…”
Section: Preparation Of Hydrolyzed Corn Starch Filmsmentioning
confidence: 99%
“…The casting technique was used to prepare films of hydrolyzed corn starch powder, glycerol, and glacial acetic acid according to the methodology of Beer-Lech et al [31]. First, 20 ± 5 g of hydrolyzed corn starch powder was mixed with 150 ± 5 mL of distilled water at 50 ± 5 • C to prepare the film-forming solution.…”
Section: Preparation Of Hydrolyzed Corn Starch Filmsmentioning
confidence: 99%
“…However, the coating of the PLA layer with TPS significantly decreased the surface wettability of the bi‐layer film. During the film forming of the TPS layer (upper side), the most hydrophobic and branched parts of the amylopectin chain in TPS are directed towards the outer surface 38 and resulted in a higher WCA value in bi‐layer films when compared with neat TPS film. The obtained results were also in accordance with WU and WVP values of mono and bi‐layer films.…”
Section: Resultsmentioning
confidence: 99%
“…Following that, 1%, 3% and 5% of Chl powder‐containing CS‐Chl x film samples showed 35.64°, 93.22° and 94.89° of WCA respectively. The similar results were also reported by previous study that the edible film made by starch and kaolinite detected higher WCA values (Beer‐Lech et al ., 2022). However, previous research has shown that adding hydrophilic substances to CS‐based composite films resulted in lower WCA (Wang et al ., 2022).…”
Section: Resultsmentioning
confidence: 99%
“…The TGA technique is an important technique used to study the thermal stability and decomposition behaviour of film‐forming materials under different temperature conditions (Beer‐Lech et al ., 2022). Figure 6 shows the thermal gravimetric analysis (TGA) and derivative thermal gravimetric analysis (DTG) curves of Chl powder, CS and CS‐Chl x films.…”
Section: Resultsmentioning
confidence: 99%